A green approach for the quantification of daptomycin in pharmaceutical formulation by UV spectrophotometry - Eliane Gandolpho Tótoli; Hérida Regina Nunes Salgado (Universidade de São Paulo, 2015)
abstract Daptomycin is the first approved drug from a new class of antimicrobials, the cyclic lipopeptides, and is a very important antimicrobial agent in current clinical practice. Currently, there are no "green" analytical methods described in the literature to analyze the typical pharmaceutical dosage form of daptomycin. Thus, the aim of this work was to validate an environment-friendly spectrophotometric method in the UV region, for the analysis of daptomycin as a lyophilized powder. Water was used as diluent and the analyses were carried out on a spectrophotometer at 221 nm. The method met all validation requirements of the ICH guidelines, over a concentration range of 6-21 µg mL-1. A Student's t-test demonstrated that the proposed method was comparable to an HPLC method previously validated. Thus, the validated spectrophotometric method could quantify daptomycin in a powder form for injectable solutions, while being an economical, rapid, and "green" alternative for routine analysis in quality control.